Pressure encryption toward physically uncopiable anti-counterfeiting - Dianlong Zhao; Shunxin Li; Yang Su; Jiajun Qin; Guanjun Xiao; Yuchen Shang; Xiu Yin; Pengfei Lv; Feng Wang; Jiayi Yang; Zhaodong Liu; Fujun Lan; et al. (Nature Communications)
Abstract Current optical anti-counterfeiting technologies are mainly limited to materials with multicolor emissions, where the encryption method is only through photoexcitation. It brings about a huge risk for counterfeiting once these materials are reproduced. Here, we introduce a robust pressure encryption as the pressure engineering secret key to strengthen current optical anti-counterfeiting technique from pressure-induced emission luminogens. Through loading different pressures, the initially non-emissive 0D hybrid halide (C7H11N2, 4DMAP)2ZnBr4 shows at least 8 different distinct bright emission colors. These color changes are attributed to controllable tuning of charge transfer and local excitation implemented by pressure treatment. Moreover, the unique color tuning through pressure loading, randomized distribution of the fluorescent particles, as well as designated micro-nano patterns greatly enhance the security capability of current visual information encryption, which serves as the triple-level physically uncopiable optical anti-counterfeiting technique. Our work provides a promising strategy of materials-by-design for high-performance anti-counterfeiting, imaging and information storage applications.